Virtual worlds and augmented reality: The enhanced reality lab as a best practice for advanced simulation and immersive learning - Fernando Salvetti; Barbara Bertagni (Firenze University Press, 2019)
e-REAL is enhanced reality for immersive simulation. It is a system where physical and digital objects co-exist and interact in real time, in a real place and not within a headset. e-REAL allows for an advanced simulation within a multisensory scenario, based on challenging situations developed by visual storytelling techniques. The e-REAL immersive setting is fully interactive with 3D holographic visualization, talking avatars, electronically writable surfaces and more: people can take notes, cluster key-concepts or fill questionnaires directly on the projected surfaces. Learners rapidly circle between deliberate practice and direct feedback within a simulation scenario until mastery is achieved. So far, the early findings show that visualization, if linked in interactive ways to the learners, allows for better neural processes related to learning and behavior change.   Mondi virtuali e realtà aumentata: l'Enhanced Reality Lab come best practice per la simulazione avanzata e l'apprendimento immersivo e-REAL è realtà potenziata per la simulazione immersiva. E' un sistema dove oggetti fisici e virtuali coesistono e interagiscono in tempo reale, in un luogo reale e non all'interno di un visore. e-REAL consente una simulazione avanzata all'interno di uno scenario multisensoriale, basato su situazioni sfidanti progettate attraverso tecniche di storytelling visuale. Il setting immersivo di e-REAL è pienamente interattivo con visualizzazioni olografiche in 3D, avatars parlanti, superfici sulle quali è possibile scrivere elettronicamente e altro ancora: le persone possono prendere note, raggruppare concetti-chiave, compilare questionari direttamente sulle superfici proiettate. L'applicazione della tecnica denominate Rapid Cicle Deliberate Practice (RCDP), basata su feedback diretti e mirati, consente di migliorare le performance già nel corso della simulazione. I primi risultati mostrano che la visualizzazione interattiva potenzia i processi neurali associati all'apprendimento e al cambiamento comportamentale.